The role of gut microbiota in the onset and development of sepsis and its therapeutic potential: mechanisms and research progress - Tian, Zhiyang; Li, Changhui (Frontiers in Microbiology, 2025)
Sepsis is a life-threatening disease triggered by infection-induced immune dysregulation, characterized by multi-organ dysfunction, and is one of the leading causes of death among critically ill patients worldwide. Recent studies have shown that gut microbiota (GM) imbalance plays a crucial role in the progression of sepsis. This review identifies the core mechanisms of GM imbalance: it disrupts the integrity of the intestinal mucosal barrier, induces bacterial and endotoxin translocation, activates systemic inflammatory responses, and forms a vicious cycle of “gut-organ” cross-damage, becoming a key driver of sepsis-associated multi-organ dysfunction. Existing research has confirmed that microbiota modulation strategies, such as probiotic supplementation and fecal microbiota transplantation (FMT), have potential therapeutic value. However, due to issues like strain specificity, lack of standardized protocols, and insufficient clinical evidence, the clinical translation of these strategies still faces significant barriers. Therefore, future research should focus on the identification of sepsis-specific GM core functional biomarkers, the development of personalized combined regulatory strategies, and the advancement of targeted delivery technologies. Multi-center large-scale clinical trials are needed to validate their efficacy and safety, providing innovative solutions for precision treatment of sepsis.